10. EXPLORING MUSLIM WOMEN'S LIVED-EXPERIENCES ON COUNTERFEIT FASHION GOODS CONSUMPTION - Rosely, Nurhidayah; Abdullah Thani, Ayu Kamareenna; Zahirah Omar, Siti Nur; Ismail, An Nur Nabila; Nik Mohd Zainordin, Nik Mohamad Shamim (Journal of Islamic, Social, Economics and Development, 2024)
Counterfeits market have been common and are a baffling global issue due to the ignorance of consumers and society normalisation on the illegal consumption practice. Hence, consumers feel that the purchase and consumption of such goods do not create any harmful effect on society, the economy, and the authentic fashion goods industry; thus, these dark markets pose the greatest challenge for fashion brand manufacturers in preventing consumers involement in counterfeiting activities. Thus, this study aims to discover Malaysian Muslim women’s purchase behaviour in counterfeit branded fashion goods and explore their consumption practices from their lived experiences. Additionally, the insights lead to the development of emerging themes, which will help comprehend Malaysian Muslim women's attitudes, behaviour, and level of consciousness on the counterfeit issue. The phenomenology approach has been used to probe into the lived experience of 6 Muslim women via purposive and snowball sampling. In-depth interviews were conducted and data were analysed using thematic analysis. Four themes emerged from this study; society norms, fear of being caught, compensating original brand and comparable quality revealed that society norms, legitimising counterfeit goods purchase, particularly on fashion goods among Muslim women. The finding validated that Muslim women found counterfeit branded fashion goods enable them to compensate their fashion consciousness needs and disregard the concept of “halal” in their consumption practice in order to keeping up with the trend and fashion. This study ultimately assisting fashion goods manufacturer to develop operative marketing strategies and mechanisms to reduce the rate of counterfeit goods purchases in Malaysia.